3 - Structural orientation and social agency in South Africa: state, race, higher education and transformation - Thaver, Lionel; Thaver, Beverley (African Sociological Review, 2010)
we have taken as our brief and context the latest upsurge in incidents of a racist nature in certain higher education institutions in South Africa. what we contribute to thinking on the subject is goldberg’s (2002) theoretical framework in which he focuses on the emergence, for- mation, existence and transformation of racial formations as constitutive of social life. In the South African context we apply this framework and its understanding of racial traditions to higher education in order to reveal the shifts across the social formations of segregation, apart- heid and constitutional democracy. Our central argument is that goldberg’s concept of racial naturalist and racial historicist traditions of social agency when applied to higher education institutions disclose legacies of a differentiated racial regime. In this regard, we take up the trajectory of racialisation as in its segregationist and apartheid modalities of state formation; its deracialisation in our post-apartheid modality of social engagement towards the non-racial project of constitutional democracy as a movement beyond the shadow of racist thinking both implicit and explicit. The thrust of our engagement is that in order to make sense of racial formations and their modalities of structural orientation and social agency we need to think of racism within the complex of a state-race-class nexus. In sum then, the argument that we make vis-à-vis the differentiated racialised orders is that we need to embed ourselves within our national, South African, and continental, African, contexts in order to challenge the racial traditions that continue to bedevil efforts towards consolidating our constitutional democracy and its concomitant epistemic project.